Effective Optimization Strategy for Electron Beam Lithography of Molecular Glass Negative Photoresist - Jiaxing Gao; Siliang Zhang; Xuewen Cui; Xue Cong; Xudong Guo; Rui Hu; Shuangqing Wang; Jinping Chen; Yi Li; Guoqiang Yang (Advanced Materials Interfaces, 2023)
Abstract As the crucial dimension (CD) of logic circuits continues to shrink, the photoresist metrics, including resolution, line edge roughness, and sensitivity, are faced with significant challenges. Photoresists are indispensable in the integrated circuit manufacturing industry, and specifically in achieving smaller critical dimensions. In this study, the effects of two categories of photosensitive compounds on lithography performance are explored, through a series of sulfonium salt‐based photoacid generators (PAGs) with diverse reactivity and photodegradable nucleophiles (PDNs) with varying nucleophilicity. The detailed characterization and exposure experiments suggest that the reactive alterations of different PAGs are mostly associated with the amount of phenyl composed of cations in PAGs. The “PDN first, PAG second” strategy, which employs a combination of low reactivity PAG and high reactivity PDN and involves PDN decomposition first and PAG decomposition second in the electron beam lithography process, achieves high sensitivity (100–270 µC cm−2), high resolution (25 nm 1:1 line/space, L/S), and low line edge roughness (LER ≤ 3.3 nm) stripes. This approach outperforms conventional formulations and may provide a potentially effective and useful strategy to improve electron beam photoresists.